2017
DOI: 10.1088/1361-6528/aa5aef
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tunneling current and local contact potential difference on the TiO2(110) surface by AFM/KPFM at 78 K

Abstract: We propose a new multi-image method for obtaining the frequency shift, tunneling current and local contact potential difference (LCPD) on a TiO(110) surface with atomic resolution. The tunneling current image reveals rarely observed surface oxygen atoms contrary to the conventional results. We analyze how the surface and subsurface defects affect the distribution of the LCPD. In addition, the subsurface defects are observed clearly in the tunneling current image, in contrast to a topographic image. To clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…In the V LCPD image (see Figure 5 c), the imaging contrast was the reverse of that in the image, except for the O ad . The relative value of V LCPD between the Ti 5c and O 2c sites was approximately 28 mV from the line profile (not shown here), and this was in good agreement with our previous studies [ 18 , 19 ]. V LCPD had a higher value on the O ad than on the proximate Ti 5c rows, and the relative value of CPD between the O ad and Ti 5c row was about 75 mV.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In the V LCPD image (see Figure 5 c), the imaging contrast was the reverse of that in the image, except for the O ad . The relative value of V LCPD between the Ti 5c and O 2c sites was approximately 28 mV from the line profile (not shown here), and this was in good agreement with our previous studies [ 18 , 19 ]. V LCPD had a higher value on the O ad than on the proximate Ti 5c rows, and the relative value of CPD between the O ad and Ti 5c row was about 75 mV.…”
Section: Resultssupporting
confidence: 93%
“…Thus, tunneling current dramatically decreases, and the contrast of O ad becomes a dark spot in < I t > image. The bright spot marked by an oval circle is due to subsurface defects, which was not probed in Figure 4 a, ever reported by our group or other groups [ 19 , 22 ]. Figure 4 c is the ∆ f image and Figure 4 d is the corresponding tunneling current image, recorded in the constant height mode.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Variations of surface potential over the scan area were observed from both samples, which might be caused by an AC voltage generally applied to the tip while scanning. KPFM though is not for a quantitative measurement of surface potential 28 , the results clearly confirmed that the electric field originating from the LiNbO 3 is significantly large and can penetrate through the ITO layer and TiO 2 film. In other words, the TiO 2 film is “immersed” in an electric field in view of the spontaneous polarization of LiNbO 3 .…”
Section: Resultsmentioning
confidence: 84%